Recurrent Acute Pancreatitis in a Patient with Wirsungocele and Neuroendocrine Tumor of Ampulla of Vater - Dhir, Vinay; Joshi, Nitin; Vivekanandarajah, Suhirdan; Bhandari, Suryaprakash; Bapat, Mukta; Maydeo, Amit (JOP. Journal of the Pancreas, 2013)
Context Wirsungocele has recently been shown to be associated with acute recurrent, severe necrotizing pancreatitis and chronic pancreatitis or chronic pain in abdomen. Till to date there is no report on association of wirsungocele with an ampullary neuroendocrine tumor, and recurrent pancreatitis. Case report We report a first ever case of wirsungocele diagnosed on EUS, its association with neuroendocrine tumor of ampulla and recurrent acute pancreatitis. Conclusion This case report highlights the diagnostic utility of EUS in diagnosing small ampullary pathology like wirsungocele and neuroendocrine tumor. Image: MRCP showing cystic dilation of terminal part of main pancreatic duct.